2017
DOI: 10.1536/ihj.16-124
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Thiol/Disulphide Homeostasis in Anthracycline Associated Cardiac Toxicity

Abstract: SummaryThe aim of the present study was to evaluate whether the baseline thiol/disulfide state can predict the occurrence of anthracycline induced cardiac toxicity. A total of 186 cancer patients receiving anthracycline (doxorubicin)-based chemotherapy were enrolled. All patients underwent 2-dimensional (2D) speckle tracking echocardiography (STE) to determine their left ventricular ejection fraction (LVEF) and blood samples for measuring thiol forms were obtained before treatment and 4 weeks after completion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
1
11
0
1
Order By: Relevance
“…The conformational and functional changes in physiological proteins occur due to the loss of -SH groups. -SH groups attempting to impede the harmful effects of free radicals might decrease the serum and tissue concentrations of these radicals (20). Thiol/disulphide status was determined in diseases such as Familial Mediterranean fever (21), fibromyalgia (22), coronary artery disease (23), non-small cell lung cancer (24).…”
Section: Discussionmentioning
confidence: 99%
“…The conformational and functional changes in physiological proteins occur due to the loss of -SH groups. -SH groups attempting to impede the harmful effects of free radicals might decrease the serum and tissue concentrations of these radicals (20). Thiol/disulphide status was determined in diseases such as Familial Mediterranean fever (21), fibromyalgia (22), coronary artery disease (23), non-small cell lung cancer (24).…”
Section: Discussionmentioning
confidence: 99%
“…In an interesting study, researchers have investigated whether TDH can predict the occurrence of anthracycline-induced cardiac toxicity. They were concluded that NT may elicit more objective data for physicians to detect which patients have high risk for cardiac toxicity [27].…”
Section: Cardiac Pathologiesmentioning
confidence: 99%
“…They also suggested that this homeostasis may be used as a prognostic marker for hospital mortality. Some studies indicate that low thiol concentrations and an imbalance in the thiol/disulfide ratio may play a pathogenic role in the formation of coronary artery ectasia (CAE), atherosclerosis, and chemotherapy-induced cardiac toxicity [1921]. In all these studies, the authors hypothesized that oxidative stress might contribute to the main mechanism of pathogenesis.…”
Section: Discussionmentioning
confidence: 99%